Prognostic associations of ECG tracings in hospitalised patients with COVID-19: a systematic review and meta-analysis protocol - Emmanuel S Baja; Antonio D Ligsay; Zypher Jude G Regencia; Jasmine S Interior; Jerremiah G Garcia; Gaius Sulpicio G Yu; Ferdinand R Gerodias (BMJ Open, 2022)
Introduction COVID-19 is a global pandemic caused by the SARS-CoV-2 virus. Although most COVID-19 cases are asymptomatic or mild, a significant number of patients experienced adverse outcomes. In addition, studies have shown that cardiac abnormalities are associated with increased mortality in hospitalised patients with COVID-19. This finding sets a precedent for the potential use of ECG tracing as an indicator of patient mortality and morbidity. This study aims to determine associations between the 12-lead ECG findings and various clinical outcomes of hospitalised patients with COVID-19, measured as incidence of endotracheal intubation, intensive care unit (ICU) admission and mortality rate.Methods and analysis An electronic literature search will identify all potentially relevant articles using specific databases and websites. The search will be limited to studies published from December 2019 to May 2021. In addition, studies will include hospitalised patients with COVID-19 with normal and abnormal 12-lead ECG findings assessed for clinical outcomes, including the incidence of endotracheal intubation, ICU admission and mortality rate. The risk of bias in individual studies will be evaluated using the Quality in Prognostic Studies tool or the Cochrane risk of bias tool. A meta-analysis will be conducted if at least two studies indicate a prognostic factor’s effect. Moreover, subgroup and sensitivity analyses will be performed accordingly to address heterogeneity. Reporting the review results will comply with the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. The quality of evidence generated will be assessed using the Grades of Recommendation, Assessment, Development and Evaluation system.Ethics and dissemination This study has been exempted from ethics review. There will be no patient or public involvement in this study. Furthermore, the findings will be disseminated via conferences, seminars, symposia and congresses on top of peer-reviewed journals.PROSPERO registration number CRD42021257155.